Pelatihan Pengelolaan Keuangan bagi Pengurus Koperasi di Kabupaten Purwakarta - Elya Dasuki, Rima (E-Coops-Day, 2024)
Financial management is very important in cooperative business activities, considering that financial reports are a form of accountability to the management stakeholders especially to members as owners. The financial report must at a minimum describe the condition of assets, liabilities, and capital stated in the balance sheet report and transaction activities with members and non-members as well as costs incurred which are stated in the business results calculation report (PHU). Cooperative financial reports must be well understood by cooperative administrators so that they can account in writing for all cooperative business activities carried out accurately. Considering the very importance of financial reports, it is necessary to provide training in preparing financial reports on an ongoing basis. The training was held by the Purwakarta Regency Cooperatives and Small and Medium Enterprises Service.